A critical and empirical analysis of the national-local ‘gap’ in public responses to large-scale energy infrastructures - Batel, S.; Devine-Wright, P. (Journal of Environmental Planning and Management, 2015)
A national-local ‘gap’ is often used as the starting point for analyses of public responses to large scale energy infrastructures. We critique three assumptions found in that literature: the public's positive attitudes, without further examining other type of perceptions at a national level; that local perceptions are best examined through a siting rather than place-based approach; that a gap exists between national and local responses, despite a non-correspondence in how these are examined. Survey research conducted at national and local levels about electricity transmission lines in the UK confirm these criticisms. Results do not support a gap between national and local levels; instead, both differences and similarities were found. Results show the value of adopting a place-based approach and the role of surveys to inform policy making are discussed.